2006
DOI: 10.1002/art.21662
|View full text |Cite
|
Sign up to set email alerts
|

CXCL16‐mediated cell recruitment to rheumatoid arthritis synovial tissue and murine lymph nodes is dependent upon the MAPK pathway

Abstract: Objective. Rheumatoid arthritis (RA) is characterized by profound mononuclear cell (MNC) recruitment into synovial tissue (ST), thought to be due in part to tumor necrosis factor ␣ (TNF␣), a therapeutic target for RA. Although chemokines may also be involved, the mechanisms remain unclear. We undertook this study to examine the participation of CXCL16, a novel chemokine, in recruitment of MNCs to RA ST in vivo and to determine the signal transduction pathways mediating this process. Conclusion. Taken together,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 69 publications
(92 reference statements)
7
107
0
Order By: Relevance
“…These results have shown that the expression of CXCL16, but not that of CX 3 CL1, is associated with colorectal carcinogenesis. Recently, remarkable elevation of soluble CXCL16 in the synovial fluids of rheumatoid arthritis patients was reported (35). It is thus interesting to see whether soluble CXCL16 in serum can also be elevated in CRC patients and is a good biomarker for prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…These results have shown that the expression of CXCL16, but not that of CX 3 CL1, is associated with colorectal carcinogenesis. Recently, remarkable elevation of soluble CXCL16 in the synovial fluids of rheumatoid arthritis patients was reported (35). It is thus interesting to see whether soluble CXCL16 in serum can also be elevated in CRC patients and is a good biomarker for prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…43 CXCL16 may function to recruit mononuclear cells into affected joints, and elevated levels of CXCL16 have been detected in SF from RA patients. 44 CD209 is a high affinity receptor for ICAM2/3 and may promote cellular adhesion of FLS cells. FCGR2A is a low-affinity Fc receptor (CD32) operating to fix complement, previously implicated in the pathogenesis of RA.…”
Section: Discussionmentioning
confidence: 99%
“…Several chemoattractants stimulate MAPK activities, which in turn are involved in the chemotactic migration of cells (35,36). We also examined the roles of ERK, p38 MAPK, and JNK on WKYMVm-induced NK cell chemotaxis.…”
Section: Wkymvm-induced Nk Cell Chemotaxis Is Mediated By Erkmentioning
confidence: 99%